The role of viral infections in exacerbations of chronic obstructive pulmonary disease and asthma. (April 2016) - Hewitt, Richard; Farne, Hugo; Ritchie, Andrew; Luke, Emma; Johnston, Sebastian L.; Mallia, Patrick
Asthma and chronic obstructive pulmonary disease (COPD) are major causes of global morbidity and mortality worldwide. The clinical course of both asthma and COPD are punctuated by the occurrence of exacerbations, acute events characterized by increased symptoms and airflow obstruction. Exacerbations contribute most of the morbidity, mortality and excess healthcare costs associated with both asthma and COPD. COPD and asthma exacerbations are frequently associated with respiratory virus infections and this has led to an intense research focus into the mechanisms of virus-induced exacerbations over the past decade. Current therapies are effective in reducing chronic symptoms but are less effective in preventing exacerbations, particularly in COPD. Understanding the mechanisms of virus-induced exacerbation will lead to the development of new targeted therapies that can reduce the burden of virus-induced exacerbations. In this review we discuss current knowledge of virus-induced exacerbations of asthma and COPD with a particular focus on mechanisms, human studies, virus–bacteria interactions and therapeutic advances.